DEGRADASI MALACHITE GREEN OXALATE SECARA FOTOLISIS DAN OZONOLISIS DENGAN PENAMBAHAN ZnO-SnO2 - Bhernama, Bhayu Gita; -, Syukri; -, Safni (Jurnal Riset Kimia, 2014)
Vol 7 No 2ABSTRACTDegradation of malachite green oxalate (MGO) compounds has been carried out by ozonolysisand photolysis methods with addition of ZnO-SnO2 as catalyst. MGO solution was analyzed bya spectrophotometer UV/Vis at 250-650 nm. The results showed that ozonolysis process fasterthan photolysis. 6 mg/L MGO can be degraded as much as 97.3% after irradiated with UV light(369 nm) within 150 minutes with the addition of 0.020 g of ZnO-SnO2. Otherwise, 99.6% of 6mg/L MGO can be degraded by ozonolysis process within 5 minutes by the addition of 0.025 gof ZnO-SnO2. Analysis of the remaining MGO solution by reverse-phase HPLC showedintermediate-substances peaks and peak height of MGO at a retention time of 3.18 mindecreased as the data obtained using a UV/Vis spectrophotometer.Keywords: degradation, MGO, photolysis, ozonolysis, ZnO-SnO2